Potensi Komoditas sebagai Peningkatan Ekonomi Desa - Muhammad Elsa Tomisa; Dewi Oktayani (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
The concept of local economic development is to explore and develop resource potential in the region to increase local economic development. The local economic development concept approach provides opportunities or opportunities for the community to play an active and innovative role in determining and managing available local resources, both natural resources and human resources as a link in the economic chain. Every region or village in Indonesia has potential in the form of commodities that are suitable for development in efforts to improve the village economy. The research method used is library research. Qualitative research generally uses a literature study approach. Data was collected by looking for articles that were relevant to the discussion. The essence of economic development is to ensure that people's income increases, as well as economic equality. Economic development can also be carried out, one of which is by developing superior commodities. Superior commodities are able to contribute to villages or regions in terms of income. Superior commodities can be a source of income for local communities and can improve community welfare. Apart from that, superior commodities can also open up new jobs and increase the capacity and skills of local communities.